Association of the Synapse-Associated Protein 97 (SAP97) Gene Polymorphism With Neurocognitive Function in Schizophrenic Patients - Xu, Xusan; Liang, Chunmei; Lv, Dong; Yin, Jingwen; Luo, Xudong; Fu, Jiawu; Yan, Haifeng; Zhou, Xia; Dai, Zhun; Zhu, Dongjian; Xiong, Susu; Lin, Zhixiong; et al. (Frontiers in Psychiatry, 2018)
The SAP97 gene is located in the schizophrenia susceptibility locus 3q29, and it encodes a synaptic scaffolding protein that interacts with the N-methyl-D-aspartate (NMDA) receptor, which is presumed to be dysregulated in schizophrenia. In this study, we genotyped a single-nucleotide polymorphism (SNP) (rs3915512) in the SAP97 gene in 1114 patients with schizophrenia and 1036 healthy-matched controls in a Han Chinese population through the improved multiplex ligation detection reaction (imLDR) technique. Then, we analyzed the association between this SNP and the patients’ clinical symptoms and neurocognitive function. Our results showed that there were no significant differences in the genotype and allele frequencies between the patients and the controls for the rs3915512 polymorphism. However, patients with the rs3915512 polymorphism TT genotype had higher neurocognitive function scores (list learning scores, symbol coding scores, category instances scores and controlled oral word association test scores) than the subjects with the A allele (P = 4.72 × 10-5, 0.027, 0.027, 0.013，respectively). Our data are the first to suggest that the SAP97 rs3915512 polymorphism may affect neurocognitive function in patients with schizophrenia.